(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
James Baldwin, a novelist, essayist, playwright and social critic, is one of the most appreciated writers of America. He was one of the first American writers and, black writer, to portray homosexuality. Baldwin argues throughout his second novel Giovanni’s Room that an honest sense of one’s gender and sexuality can only be attained through a personal journey that involves more than just movement from one point to another it must also lead to a change within and an acceptance of self. In Giovanni’s Room (1956), the main character David travels a journey devoid of personal growth and acceptance. A white, homosexual man, David finds himself trapped in a white, straight, masculine American ideal which does not define him. He spends the novel trying to outrun and reject his past and that aspect of his gender identity which he wishes to ignore. Baldwin establishes self-reflection to be the only means of creating a gender identity that is able to balance acceptance with self-invention. Baldwin’s believes that every American must undertake an honest journey of self-discovery in order to establish an inclusive rather than exclusive gender identity.